2017
DOI: 10.1007/s10805-017-9278-x
|View full text |Cite
|
Sign up to set email alerts
|

How Prevalent is Contract Cheating and to What Extent are Students Repeat Offenders?

Abstract: Contract cheating, or plagiarism via paid ghostwriting, is a significant academic ethical issue, especially as reliable methods for its prevention and detection in students' assignments remain elusive. Contract cheating in academic assessment has been the subject of much recent debate and concern. Although some scandals have attracted substantial media attention, little is known about the likely prevalence of contract cheating by students for their university assignments. Although rates of contract cheating te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(55 citation statements)
references
References 18 publications
5
49
1
Order By: Relevance
“…For example, in an analysis of students looking to purchase computer code from third-parties, Clarke and Lancaster (2006) found that only 8.1% of the 236 identified contract cheaters engaged in this activity on a single occasion, compared to the 2.5% of the offenders who had engaged in this activity between 51 and 200 times in a two-month period. Curtis and Clare (2017) found that 62.5% of students who reported engaging in contract cheating across a number of self-report academic misconduct surveys indicated that they had done so on multiple occasions. Furthermore, in another self-report survey asking about engaging in contract cheating, Bailey, Tomar, and Chu (2012) reported that 3.7% of the students surveyed admitted partaking once or twice, while 3.2% admitted contracting cheating three or more times.…”
Section: Opportunity and Offending: Does What We Know About Crime Promentioning
confidence: 99%
“…For example, in an analysis of students looking to purchase computer code from third-parties, Clarke and Lancaster (2006) found that only 8.1% of the 236 identified contract cheaters engaged in this activity on a single occasion, compared to the 2.5% of the offenders who had engaged in this activity between 51 and 200 times in a two-month period. Curtis and Clare (2017) found that 62.5% of students who reported engaging in contract cheating across a number of self-report academic misconduct surveys indicated that they had done so on multiple occasions. Furthermore, in another self-report survey asking about engaging in contract cheating, Bailey, Tomar, and Chu (2012) reported that 3.7% of the students surveyed admitted partaking once or twice, while 3.2% admitted contracting cheating three or more times.…”
Section: Opportunity and Offending: Does What We Know About Crime Promentioning
confidence: 99%
“…Jones, 2008;McCabe et al, 2001;Murdock and Anderman, 2006;Rigby et al, 2015;Simkin and McLeod, 2010). Curtis and Clare (2017) argue that contract cheating is declining due to increased detection tools and associated sanctioning, while prior studies (e.g. Jones, 2008;Rigby et al, 2015) claim the opposite.…”
Section: Contract Cheatingmentioning
confidence: 99%
“…It was ascertained that it would be harmful to society as it will be filled with individuals that are inefficient members of the labour force with the propensity to cheat. Indeed, a study conducted by Curtis and Clare (2017) noted that among the number of individuals they found to have engaged in ghostwriting, 62.5% of those students did so more than once. However, the respondents noted that this cheating culture will not be limited to the academic environment alone but will become a large part of every facet of the individual's life, thus leading to continued corruption in the Nigerian society.…”
Section: P2: "For the University If There Is A Mass Number Of Studenmentioning
confidence: 99%
“…In lieu of the traditional aspects of plagiarism such as cut and paste which is largely detected by electronic text matching software (such as Google or Turnitin.com), there is a focus on the steadily increasing and more elusive forms of non-traditional types of plagiarism such as contract cheating and ghostwriting (McGowan, 2005, p. 287;Weber-Wulff, 2014;Curtis & Clare, 2017). Both concepts are similar in that they both constitute outsourcing a work to a third-party (ghostwriter or a contractor) who is paid while the original produced work is attributed to the client only (Lancaster & Clarke, 2007, p. 1;Clark & Lancaster, 2006;Exposito et al, 2015, p. 9;Singh & Remenyi, 2016, p. 2).…”
mentioning
confidence: 99%